2000
DOI: 10.1287/orsc.11.5.509.15199
|View full text |Cite
|
Sign up to set email alerts
|

Is Organization Theory Obvious to Practitioners? A Test of One Established Theory

Abstract: Critics have argued that organization theories which “work” are obvious to practitioners; that is, the theories simply confirm relationships that are already well understood by experienced managers. In our study, four types of respondents—Chief Executive Officers (CEOs) with business school education, CEOs without such education, graduating MBA students, and liberal arts graduate students—were presented with theory-based performance-rating tasks. These tasks identified respondents' beliefs regarding high-perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 70 publications
1
55
0
Order By: Relevance
“…This result elaborates on suggestions that the content of management education shapes management cause maps and mental models (Priem & Rosenstein, 2000). The fact that education content does make a difference may also suggest that business schools and scholars need to think carefully about the consequences of what they are teaching in order to avoid damaging outcomes.…”
Section: Insert Table 11 About Herementioning
confidence: 62%
See 1 more Smart Citation
“…This result elaborates on suggestions that the content of management education shapes management cause maps and mental models (Priem & Rosenstein, 2000). The fact that education content does make a difference may also suggest that business schools and scholars need to think carefully about the consequences of what they are teaching in order to avoid damaging outcomes.…”
Section: Insert Table 11 About Herementioning
confidence: 62%
“…However, Shipper's (1999) study found no real differences between MBAs and their non-MBAs counterparts in terms of managerial skills, albeit that his findings were developed from a survey of 1000 managers in a single large USA company. By contrast, Priem and Rosenstein (2000) found that MBA graduates hold cause maps that are closer to theory compared with practitioners without postgraduate education or without any management education. Thus, the experience of having formal management education and also the level of education, in terms of undergraduate or postgraduate education appear to be important within the management education concept.…”
Section: Research Modelmentioning
confidence: 74%
“…The idea that practitioners attend business school for the purposes of getting a value-adding qualification in the job market that they then abandon on the basis that it is too irrelevant to actually use in practice is surely ludicrous. Furthermore, it is not supported by the limited empirical research into uses of theory in practice, which indicates that practitioners do use our theories, albeit not necessarily in the way they were taught in business school (Baruch and Peiper, 2000;Cheng 2000;Hay and Hodgkinson 2008;Ishida 1997;2009;Kretovics 1999;Priem and Rosenstein 2000;Simpson et al 2005;Sturges et al 2003;Wren et al 2007). Rather, it is likely that theories are used because they have technical, cultural and linguistic legitimacy that makes them easily appropriable (Campbell 1997).…”
Section: Theoretical Challenges Of Taking Practice Seriouslymentioning
confidence: 99%
“…"Schools are only as good as the quality of faculty, the professional development that supports their learning, and the faculty's capacity to work together to improve instruction" (Bryk, 2010, p. 24). Priem and Rosenstein (2000) suggest that effective leaders align people, support systems, and job design in accordance with the organization's vision to boost performance.…”
Section: Operationalizing the Pimrs Dimensions And Continued Relevancymentioning
confidence: 99%
“…Effective leaders align staff incentives with the organization's vision and goals (Priem & Rosenstein, 2000).…”
Section: Protects Instructional Timementioning
confidence: 99%